Electrical and optical switching in the bistable regime of an electrically injected polariton laser - Klaas, M. (2017)
We report on electrically and nonresonant optically induced switching in the bistable regime of an electrically pumped polariton laser. Electrical switching effects can be observed by adding controlled noise in the electrical pump of the system. Noise is expected to influence the hysteresis characteristics of a bistable device and determines its application robustness. We find that the hysteresis width decreases symmetrically with a linear dependency until we observe a quenching of the bistability at a certain noise level and the output of the system becomes monostable. Furthermore, we explore the possibility to switch between the two bistable branches by a nonresonant optical pulse. Our experimental findings can be described by a set of rate equations modeling the population dynamics with additional noise terms.